Cardiopreventive effects of mitochondrial dynamics modulators in pre-diabetic rats subjected to cardiac ischaemia-reperfusion injury. (25th November 2020) - Maneechote, C; Palee, S; Jaiwongkam, T; Kerdphoo, S; Chattipakorn, S.C; Chattipakorn, N
Abstract: Background: Chronic exposure to a high-fat diet (HFD) consumption causes alteration of cardiac mitochondrial dynamics and function, leading to the abnormal left ventricular (LV) function. Since excessive mitochondrial fission and reduced mitochondrial fusion are correlated with both obesity and myocardial ischaemia, targeting mitochondrial fission and fusion could be an effective cardioprotective strategy. We previously showed that acute inhibition of mitochondrial fission and promotion of mitochondrial fusion exerted cardioprotection in obese rats. However, the chronic treatment with mitochondrial fission inhibitor (Mdivi-1) and mitochondrial fusion promoter (M1) in pre-diabetic rats subjected to cardiac ischaemia-reperfusion (I/R) injury has never been investigated. Purpose: We investigated the cardiopreventive effects of chronic Mdivi-1 and M1 treatment in pre-diabetic rats with cardiac I/R injury on infarct size, mitochondrial function, and LV contractility. Methods: Wistar rats (n=32, male) were fed with HFD for 12 weeks, then randomly divided into: 1) HFV (Vehicle, 0.1% DMSO), 2) HFMdivi1 (Mdivi-1, 1.2 mg/kg), and 3) HFM1 (M1, 2 mg/kg) with intraperitoneal injection. After 2 weeks of drugs administration, all rats underwent 30 min of left anterior descending coronary artery occlusion followed by reperfusion for 120 min. LV function was monitored throughout the experiment. At the end, the heart was removed to determine infarct size and mitochondrial function. Results: Chronic treatment with Mdivi-1 and M1 similarly showed a decrease in mitochondrial reactive oxygen species and infarct size, leading to an improvement in LV function in HFD rats, as indicated by increased ejection fraction, when compared to HFV rats (Figure). Conclusion: Mitochondrial fission inhibitor and fusion promoter exerted similar efficacy in protecting pre-diabetic rat hearts against cardiac I/R injury through attenuating mitochondrial dysfunction, reducing infarct size and increasing LV contractility. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): The National Science and Technology Development Agency Thailand